(untitled) - Spanckeren, Kathryn Van; Kathryn VanSpanckeren (Washington, D.C., 2001)
American literature begins with the orally transmitted myths, legends, tales, and lyrics (always songs) of Indian cultures. There was no written literature among the more than 500 different Indian languages and tribal cultures that existed in North America before the first Europeans arrived. As a result, Native American oral literature is quite diverse. Narratives from quasi-nomadic hunting cultures like the Navaho are different from stories of settled agricultural tribes such as the pueblo dwelling Acoma; the stories of northern lakeside dwellers such as the Ojibwa often differ radically from stories of desert tribes like the Hopi
Keywords: American literature; Authors